Risiko Infeksi Plasmodium Falciparum dalam Kehamilan terhadap Perkembangan Bahasa Reseptif dan Ekspresif pada Anak Balita - Astutik, Eftyaningrum Dwi Wahyu (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the relationship between Plasmodium Falciparum infection in pregnancy and impaired receptive and expressive language development in children under five. The research method uses an observational analytical design with a case-control approach. The results of the study showed that there was no significant relationship between a history of plasmodium falciparum infection in pregnancy and receptive language disorders in children under five, and there was no meaningful relationship between a history of plasmodium falciparum infection in pregnancy and expressive language disorders in children under five. In conclusion, a history of Plasmodium falciparum infection during pregnancy is not associated with impaired receptive and expressive language development in children under five. Keywords: Expressive, Pregnancy, Language Development, Plasmodium Falciparum, Receptive